KETERLIBATAN MASYARAKAT DALAM PENGEMBANGAN USAHA PARIWISATA DI WANA WISATA KAWAH PUTIH (Jurnal Ilmiah Pariwisata; Vol 20 No 1 (2015), 2015)
This study aims to determine the community's involvement in the development of tourism business at Wana Wisata Kawah Putih, Kaupaten Bandung. The method used is descriptive-qualitative by using the Nominal Group Technique (NGT) as a guide to analyze. Data were obtained from observations and interviews with informants purposively. The conclusion that the community is involved in functional or collaboration level.
Keywords: Community' s involvement, Tourism Development, Tourism Business, Nominal Group Technique.